A novel fluorescence polarization assay for copper ions based on DNA-templated click chemistry and amplification of nanoparticles. Issue 88 (8th December 2017) - Liao, Suqi; Zhao, Jingjin; Qin, Yingfeng; Zhao, Shulin
Abstract : An amplified FP assay for Cu 2+ based on DNA-templated click chemistry and SA-SiO2 was developed. Abstract : In this work, we developed a novel fluorescence polarization (FP) method for the sensitive detection of Cu 2+ based on the chemical ligation of DNA by click chemistry and silica nanoparticles-assisted FP enhancement. A double-stranded DNA hybrid (P1P2) is used as an "end-of-helix" template with an alkyne group and an azide group at the end of two DNA strands, respectively. Cu 2+ can be reduced to Cu + by sodium ascorbate, and trigger the chemical ligation P1P2 through the Cu + -catalyzed azide–alkyne cycloaddition. A biotin-labeled P3 which can hybridize with P1 is introduced to displace the FAM-contained P2 from P1P2 duplex. Since P1 and P2 are linked after the Cu 2+ -triggered click chemistry, a P1P2P3 complex is formed which can be captured on the silica nanoparticle surface through the biotin-streptavidin interaction, thus achieving a high FP signal. In the absence of Cu 2+, there is no ligation between P1 and P2. The released P2 is free and cannot be immobilized on the nanoparticle surface, resulting in a low FP. The specificity of click chemistry provides a high selectivity, and the nanoparticle-assisted FP enhancement provides a high sensitivity with a detection limit of 0.0178 μM. This method also displays good assay performance in real water samples, which may be further used for environmental monitoring.